Peningkatan Pemahaman Masyarakat Tentang Perlindungan Hukum Sumberdaya Genetik Di Sekitar Taman Nasional Lore Lindu - Lanini, Agus; Ikhsan Syafiuddin , Ikhsan; Budimah, Budimah (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2026)
Improving communities concience regarding the legal protection of genetic resources as an instrument for environmental conservation is an urgent activity, particularly to empower farmer groups who are highly vulnerable to various problems. This is exacerbated by a lack of public understanding regarding the prohibition on illegal logging, including the permissibility of illegal logging in the area. Given this situation, legal awareness is crucial, particularly regarding the legal obligation to conserve forests, especially in forest areas. The community of Pakuli Village, Gumbasa District, Sigi Regency, needs to understand this to foster a harmonious relationship between the environment and humans. The activity began with field observations, followed by contact with the neighborhood unit (RW) head for administrative purposes, scheduling activities, and inviting prospective participants to the training. Lectures and interactive dialogues were held in the afternoon, as this time would not disrupt residents' work. It can be concluded that the community's low level of understanding regarding the legal protection of genetic resources is due to a lack of information/socialization regarding the prohibition on illegal logging, including the permissibility of illegal logging in the area.